Nourishing the Infant Gut Microbiome to Support Immune Health: Protocol of SUN (Seeding Through Feeding) Randomized Controlled Trial. - Wall CR; Roy NC; Mullaney JA; McNabb WC; Gasser O; Fraser K; Altermann E; Young W; Cooney J; Lawrence R; Jiang Y; Galland BC; et al. (JMIR Publications, 2024)
Background: The introduction of complementary foods during the first year of life influences the diversity of the gut microbiome. How this diversity affects immune development and health is unclear. Objective: This study evaluates the effect of consuming kūmara or kūmara with added banana powder (resistant starch) compared to a reference control at 4 months post randomization on the prevalence of respiratory tract infections and the development of the gut microbiome. Methods: This study is a double-blind, randomized controlled trial of mothers and their 6-month-old infants (up to n=300) who have not yet started solids. Infants are randomized into one of 3 groups: control arm (C), standard kūmara intervention (K), and a kūmara intervention with added banana powder product (K+) to be consumed daily for 4 months until the infant is approximately 10 months old. Infants are matched for sex using stratified randomization. Data are collected at baseline (prior to commencing solid food) and at 2 and 4 months after commencing solid food (at around 8 and 10 months of age). Data and samples collected at each timepoint include weight and length, intervention adherence (months 2 and 4), illness and medication history, dietary intake (months 2 and 4), sleep (diary and actigraphy), maternal dietary intake, breast milk, feces (baseline and 4 months), and blood samples (baseline and 4 months). Results: The trial was approved by the Health and Disability Ethics Committee of the Ministry of Health, New Zealand (reference 20/NTA/9). Recruitment and data collection did not commence until January 2022 due to the COVID-19 pandemic. Data collection and analyses are expected to conclude in January 2024 and early 2025, respectively. Results are to be published in 2024 and 2025. Conclusions: The results of this study will help us understand how the introduction of a specific prebiotic complementary food affects the microbiota and relative abundances of the microbial species, the modulation of immune development, and infant health. It will contribute to the expanding body of research that aims to deepen our understanding of the connections between nutrition, gut microbiota, and early-life postnatal health. Trial Registration: Australian New Zealand Clinical Trials Registry ACTRN12620000026921; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=378654 International Registered Report Identifier (IRRID): DERR1-10.2196/56772 JMIR Res Protoc 2024;13:e56772
Keywords: RTI; complementary feeding; complementary food; feeding; gut microbiome; gut microbiota; immune; immune development; immune system; infancy; infant; infant health; kūmara; microbiome; prevalence; respiratory tract infections; Female; Humans; Infant; Male; Double-Blind Method; Gastrointestinal Microbiome; Infant Nutritional Physiological Phenomena; Musa; New Zealand; Respiratory Tract Infections; Randomized Controlled Trials as Topic